Ozone therapy of the adenomyosis at women with sterility and hypothyroidism - Avramenko, Natalia; Barkovskiy, Dmitro; Postolenko, Viktoriya (ScienceRise: Medical Science, 2017)
Aim of research – specification of hormonal-immunologic shifts and increase of the effectiveness of sterility treatment in patients with adenomyosis and hypothyroidism. Materials and methods. There were examined 90 women with the primary sterility, who participated in the program of auxiliary reproductive technologies (ART) – extracorporal fertilization ART, among them 60 with adenomyosis and hypothyroidism (main group), the control group included 30 patients without thyroid pathologies without gynecological diseases. The main group was divided in 2 clinical groups: 30 patients, who underwent the traditional treatment and 30 whom the ozone therapy was additionally prescribed to. The methods of ultrasound examination, MRT, determination of the hormonal and immunologic status, cytokines state before and after the treatment were used. Results. At adenomyosis at the background of hypothyroidism were determined the changes of hypophysis and ovary function that may be caused by the increase of thyrotropic hormone (TTG), follicles stimulating hormone (FSH), luteinizing hormone (LH) and prolactin secretion. Adenomyosis, associated with hypothyroidism disturbs the cellular and humoral immunity, favors shifts in the cytokine link of immunity. At the further observation over patients of the main group, the ART extracorporal fertilization program demonstrated its more effectiveness in sterility treatment by the ozone therapy (26,7 %), comparing with the traditional treatment (16,6 %). Conclusions. The use of ozone therapy favors normalization of hormonal and immune parameters in women with adenomyosis and thyroid pathology, resulting in the increase of auxiliary reproductive technologies (ARD) effectiveness